2013
DOI: 10.1093/abbs/gms113
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of MTA1 protein leads to the inhibition of migration, invasion, and angiogenesis of non-small-cell lung cancer cell line

Abstract: Metastasis-associated protein 1 (MTA1) high expression has been detected in a wide variety of human aggressive tumors and plays important roles in the malignant biological behaviors such as invasion, metastasis, and angiogenesis. However, the specific roles and mechanisms of MTA1 protein in regulating the malignant behaviors of non-small-cell lung cancer (NSCLC) cells still remain unclear. To elucidate the detailed functions of MTA1 protein, we down-regulated the MTA1 protein expression in NSCLC cell line by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…However, the mechanism of miR-30c requires further research. MTA1 was an integral component of NuRD complex, and played an important role in invasive, as the same result of our study [29,30]. Overexpression of MTA1 was reported in carcinogenesis in human colorectal, breast, and lung cancers; it was a prognostic indicator and was associated with poor survival in esophageal, breast, and urinary cancers [31].…”
Section: Discussionsupporting
confidence: 85%
“…However, the mechanism of miR-30c requires further research. MTA1 was an integral component of NuRD complex, and played an important role in invasive, as the same result of our study [29,30]. Overexpression of MTA1 was reported in carcinogenesis in human colorectal, breast, and lung cancers; it was a prognostic indicator and was associated with poor survival in esophageal, breast, and urinary cancers [31].…”
Section: Discussionsupporting
confidence: 85%
“…The invasion assay was performed using transwell chambers (Corning, New York, USA) with 50  μ L Matrigel-precoated (BD, San Diego, USA) polycarbonate membrane (8.0  μ m pore size) as described in the previous report [35]. Briefly, cells were collected and resuspended in the serum-free RPMI 1640 medium at a concentration of 1 × 10 5  cells/mL, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study demonstrated that MTA1 plays a key role in the regulation and mediation of the invasive phenotypes of lung cancer cells, and it has been reported that this regulation functions by altering the expression of miR [14]. However, the mechanism by which MTA1 protein regulates the malignant progression of NSCLC is not well understood [17]. …”
Section: Introductionmentioning
confidence: 99%